2010
DOI: 10.1083/jcb.201001136
|View full text |Cite
|
Sign up to set email alerts
|

JunB transcription factor maintains skeletal muscle mass and promotes hypertrophy

Abstract: Decreasing JunB expression causes muscle atrophy, whereas overexpression induces hypertrophy and blocks atrophy via myostatin inhibition and regulation of atrogin-1 and MuRF expression via FoxO3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 49 publications
(134 reference statements)
8
112
1
Order By: Relevance
“…Specifically, it was reported that the muscle hypertrophy resulting from myostatin inactivation or overexpression of Akt occurred without the recruitment of satellite cells (Amthor et al, 2009;Blaauw et al, 2009). More recently, Raffaello and colleagues (Raffaello et al, 2010) showed that overexpression of the transcription factor JunB increased mean cross-sectional area by ~40% and did not involve satellite cells, as assessed by BrdU labeling of myonuclei (Raffaello et al, 2010). Consistent with these studies, we found, in satellite celldepleted muscle undergoing hypertrophy, no change in the number of myonuclei per fiber, which was accompanied by a dramatic reduction (~80%) in BrdU + myonuclei.…”
Section: Research Articlesupporting
confidence: 79%
“…Specifically, it was reported that the muscle hypertrophy resulting from myostatin inactivation or overexpression of Akt occurred without the recruitment of satellite cells (Amthor et al, 2009;Blaauw et al, 2009). More recently, Raffaello and colleagues (Raffaello et al, 2010) showed that overexpression of the transcription factor JunB increased mean cross-sectional area by ~40% and did not involve satellite cells, as assessed by BrdU labeling of myonuclei (Raffaello et al, 2010). Consistent with these studies, we found, in satellite celldepleted muscle undergoing hypertrophy, no change in the number of myonuclei per fiber, which was accompanied by a dramatic reduction (~80%) in BrdU + myonuclei.…”
Section: Research Articlesupporting
confidence: 79%
“…2A,B). Consistent with this finding, JunB has been associated with cell lineage specification and differentiation in several cell types, including in hematopoietic stem cells (Santaguida et al, 2009), T cells (Son et al, 2011), osteoblasts (Guo et al, 2014) and skeletal muscle cells (Raffaello et al, 2010). Moreover, mice that are homozygous null for JunB die between E8.5 and E10 due to impaired placental development, and although cell proliferation is normal in JunB-null embryos, retarded embryo growth may reflect failure to establish maternal circulation (Schorpp-Kistner et al, 1999).…”
Section: Neurovascular Interactions In Developing Embryonic Mouse Limsupporting
confidence: 54%
“…However, for Ski and myostatin the hypertrophy is not fully functional, as the specific force is reduced (Amthor et al, 2007;Charge et al, 2002;Mendias et al, 2011). Although it was not measured, the same is probably true for junB, as it might also act by inhibiting myostatin (Raffaello et al, 2010).…”
Section: The Textbook Model For Muscle Size Regulationmentioning
confidence: 98%
“…More recently, the debate was rejuvenated by several transgenic models displaying large fibres without a corresponding increase in the number of myonuclei, such as mice overexpressing the proteins Ski (Bruusgaard et al, 2005), Akt (Blaauw et al, 2009) or junB (Raffaello et al, 2010), as well as myostatin-null mice (Amthor et al, 2009). However, for Ski and myostatin the hypertrophy is not fully functional, as the specific force is reduced (Amthor et al, 2007;Charge et al, 2002;Mendias et al, 2011).…”
Section: The Textbook Model For Muscle Size Regulationmentioning
confidence: 99%